2019
DOI: 10.1080/13102818.2019.1696702
|View full text |Cite
|
Sign up to set email alerts
|

Single-strand DNA breaks and oxidative changes in rat testes exposed to radiofrequency radiation emitted from cellular phones

Abstract: The testes are a sensitive organ to electromagnetic pollution and people are concerned about the harmful effects of the radiofrequency radiation (RFR) emitted from cellular phones. Therefore, the purpose of this study was to investigate the effects of long-term exposure to different RFR frequencies on single-strand DNA breaks and oxidative changes in rat testicular tissue. Twenty-eight male Sprague-Dawley rats were divided randomly into four groups. Three groups were exposed to radiation emitted from 900, 1800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…The average whole-body SAR values for 1800 and 2100 MHz are 0.62 and 0.20 W/kg, respectively (SAR value was determined as described by Alkis et al [2019b]). The EMR 300 field probe was used to calculate the EMF values near and around the antenna.…”
Section: Speci¢c Absorption Rate (Sar) Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average whole-body SAR values for 1800 and 2100 MHz are 0.62 and 0.20 W/kg, respectively (SAR value was determined as described by Alkis et al [2019b]). The EMR 300 field probe was used to calculate the EMF values near and around the antenna.…”
Section: Speci¢c Absorption Rate (Sar) Measurementsmentioning
confidence: 99%
“…In addition, recently it has been preferred to use wireless Bluetooth or corded headsets instead of connecting cell phones directly to the ear. However, when people use a cell phone in this way, they usually carry the phone in the front pocket of the pants, in the hand, or on the belt [Alkis et al, 2019b]. Thus, the liver remains under the influence of cell phone radiation in speech mode for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Malondialdehyde (MDA) is a final lipid peroxidation product that has toxic effects on tissues such as the kidney, liver, blood, heart, brain and spermatozoa after exposure to EMR (Adebayo, Adeeyo, Ogundiran, & Olabisi, 2019; Berköz et al., 2018). Gonads are sensitive to environmental stresses such as EMR and heat (Alkis, Akdag, Dasdag, Yegin, & Akpolat, 2019). Many studies show that EMR exposure can affect on the quality of semen and reduce sperm count, change sperm motility and histological structure of seminiferous tubule, finally leading to infertility in human and animal model (Al‐Bayyari, 2017; Gautam et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to study of Alkis et al, the testis is the most sensitive organ to EMF pollution, and they researched the effects of 900, 1800 and 2100 MHz RF exposure on testicular tissue for 6 months. They found that RF exposure caused to increasing total oxidant status, oxidative stress index, malondialdehyde and DNA single-strand breaks in the testicular tissue especially at 1800 and 2100 MHz frequencies [4].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, especially its long term effects cause some detrimental effects on male fertility [3]. RF and microwave radiations emitted from mobile phones may lead to infertility for reasons such as single and double strand DNA breaks, decrease in sperm concentrations, seminiferous tubule diameters and serum testosterone levels, reduction in sperm vitality and motility, increased in reactive oxygen species (ROS) [4].…”
Section: Introductionmentioning
confidence: 99%